Sperm Whale Physeter macrocephalus stranded at Devbagh beach, Karwar, western coast of India - U.G. Naik; J.L. Rathod; S.B. Haragi (Journal of Threatened Taxa, 2010)
A stranding of a single Sperm Whale Physeter macrocephalus was recorded at the Devbag beach (Arabian Sea), Karwar, Karnataka State, on the central west coast of India on 17th September 2009. As it occurred in the hours of darkness, a rescue operation could not be made, resulting in the death of the live-stranded animal. Species identification was carried out using morphometric measurements. Death was found to have resulted from natural causes, the unusually low tide was probably the cause of the stranding.